Efficacy of small-incision lenticule extraction surgery in high astigmatism: A meta-analysis - Cui, Ge; Di, Yu; Yang, Shan; Chen, Di; Li, Ying (Frontiers in Medicine, 2023)
Abstract Purpose: To evaluate the efficacy of small incision lenticule extraction (SMILE) on improving vision and visual quality and correcting astigmatism for the treatment of high astigmatism. Methods: Eligible researches were identified in PubMed, Embase, and the Cochrane Central Register of Controlled Trials, searched from inception to 29 May, 2022, studies comparing the efficacy of SMILE with femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK) or transepithelial photorefractive keratectomy (T-PRK) for high astigmatism (≥ 2.00 diopters). The references of all searched literature were checked as supplements. Eligible studies were appraised for risk of bias, and synthesized. Literature was screened according to the inclusion and exclusion criteria and relative data were extracted. Data were extracted and analyzed by Review Manager 5.4. The primary outcome was postoperative uncorrected distance visual acuity (UDVA). The secondary outcomes included corneal aberrations and vector parameters. The weight mean difference (WMD), and their 95% confidence intervals (95% CI) were used to assess the strength of the association. Results: Six studies including 380 astigmatism eyes were involved, with 211 high astigmatism eyes and 31 low astigmatism eyes undergoing SMILE surgery, 94 high astigmatism eyes receiving FS-LASIK surgery, 44 high astigmatism eyes taking T-PRK surgery. Compared with non-SMILE, SMILE induced more astigmatism (weighted mean difference [WMD] = -0.07, 95% CI [-0.12 to -0.02], P = .005) and less sphere aberrations (WMD = -0.12, 95% CI [-0.17 to -0.08], P ＜0.00001), The postoperative UDVA, sphere, spherical equivalent, and higher order aberrations in different surgeries were likewise equivalent. The difference vector and index of success were significantly higher, and the surgically induced astigmatism vector, correction index, and magnitude of error were significantly lower in SMILE. Conclusions: This meta-analysis suggests that SMILE, FS-LASIK and T-PRK show excellent efficacy, predictability, and safety for myopia. SMILE exhibited less astigmatism refraction predictability and less surgically induced spherical aberrations. There maybe more under correction in SMILE. More randomized, prospective, and large sample-sized studies are needed to confirm these conclusions in the long term.